2018
DOI: 10.1093/eurpub/cky032
|View full text |Cite
|
Sign up to set email alerts
|

Deciding on cystic fibrosis carrier screening: three citizens’ juries and an online survey

Abstract: BackgroundHealth technology assessment and ethical issues have to be dealt with in deciding on national carrier screening for cystic fibrosis (CF)—the most frequent severe autosomal recessive disease in Caucasian populations and several stakeholders need to be involved. A citizens’ jury is one way to ask citizens to deliberate on controversial topics in the interests of a society. The aims of this project were to gather opinions about CF carrier screening through citizens' jury deliberations and to match them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…The result shows that the jury believed that they had more knowledge about the advantages and disadvantages of PSA screening than the control group; the jury recommended alternative government programs to support general practitioners in providing enough information to the public to allow them to consider positive and negative impacts and make an informed decision. Mosconi et al’s ( 2018 ) case regarding cystic fibrosis carriers screening demonstrated that even using online surveys, it is possible to deliberate broad and interesting insight into public perceptions and opinions if the jury is provided enough information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result shows that the jury believed that they had more knowledge about the advantages and disadvantages of PSA screening than the control group; the jury recommended alternative government programs to support general practitioners in providing enough information to the public to allow them to consider positive and negative impacts and make an informed decision. Mosconi et al’s ( 2018 ) case regarding cystic fibrosis carriers screening demonstrated that even using online surveys, it is possible to deliberate broad and interesting insight into public perceptions and opinions if the jury is provided enough information.…”
Section: Resultsmentioning
confidence: 99%
“…Under the medical care theme, the author encountered and analyzed a host of controversial topics including the availability of health screening and age restrictions, cystic fibrosis screening (Mosconi et al 2018 ), controversial prostate-specific antigen screening (PSA; Rychetnik et al 2014 ), controversial designer DNA testing for diseases in unborn babies (Iredale and Longley 2007 ), prioritization of immunization programs (Parrella et al 2016 ), and mammography examinations of women between 70–74 years old (Degeling et al 2018 ). For example, regarding PSA screenings, while there is a possibility of increasing the survival rate, there is also concern that unnecessary treatment of prostate cancer may increase the burden on the body (Rychetnik et al 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Three citizen juries, a method of deliberative democracy to engage citizens in health decision making, were in favor of screening. In addition, an online public consultation found that the general public (86%) and health workers (63%) believe that the National Health Service should provide CF RCS …”
Section: Italymentioning
confidence: 99%
“…Il bilancio di benefici e costi è stato giudicato positivo. Nell'indagine online, la popolazione generale e le persone con casi in famiglia erano chiaramente a favore dello screening, mentre i medici risultavano più critici rispetto al rapporto costi/benefici [3]. Anche in considerazione di questi risultati, Fondazione ha scelto di impegnarsi in un progetto strategico che approfondisse vantaggi e rischi di un'offerta diffusa del test del portatore e migliorasse la consapevolezza delle caratteristiche della malattia e del test.…”
unclassified